EXPERIMENTAL STUDY OF THE SYENITIC ROCKS FROM THE YAMATO AND SØR RONDANE MOUNTAINS, EAST ANTARCTICA - オオバ, タカノブ; シライシ, カズユキ; OBA, Takanobu; SHIRAISHI, Kazuyuki (National Institute of Polar Research, 1990)
P(論文) The melting relationships of five syenites from the Yamato and Sør Rondane Mountains were determined in the temperature range of 650-850℃, under the water pressure of 1-2 kbar and oxygen fugacities of the FMQ buffer. The syenites studied are samples from the Yamato Mountains (Nos. 73120904 : Y904 and 73120405 : Y405) and from the Sør Rondane Mountains (Nos. 85012101A : SR-A, 85012103B : SR-B and 85012103C : SR-C). They are composed of porphyritic K-feldspar, plagioclase, quartz, biotite, Ca-amphibole or Ca-Na amphibole, clinopyroxene, sphene, ilmenite and rarely magnetite. Though the syenites from both regions consists of the same mineral assemblages, the compositions of amphiboles are various as follows; Ca-amphibole in the syenite (Y904) from the Yamato Mountains is close to edenitic. On the other hand, the bluish green hornblende in the mafic layer (SR-B) and the leucocratic layer (SR-C) from the Sør Rondane Mountains is richteritic actinolite. In the porphyritic syenite (Y405) and the leucocratic syenite (SR-A) intruding the layered syenites (SR-B and SR-C), the Ca-amphibole is pargasitic hornblende. The solidus temperatures of the syenites from the Sør Rondane Mountains are about 770℃ at 1 kbar. With increasing temperature, plagioclase (albite) and quartz disappeared in the lower temperature range than K-feldspar, hornblende, biotite and clinopyroxene. Clinopyroxene, biotite and K-feldspar are stable at 850℃ under the water pressure of 1 kbar. Richteritic actinolite in two layered syenites (SR-B and SR-C) becomes unstable at slightly higher temperature than solidus at 1 kbar. Pargasitic hornblende from syenite (SR-A) is stable at 825℃ and 1 kbar, and it disappears at 775℃ and 1.7 kbar. Representative results of syenites from the Yamato Mountains at 1 kbar are : clinopyroxene quartz syenite (Y904) begins to melt at 680℃, quartz and plagioclase disappear at 710℃, edenitic hornblende disappears at 775℃, K-feldspar disappears at 825℃, clinopyroxene hornblende quartz syenite (Y405) begins to melt at ...